ABDOMINAL COMPARTMENT SYNDROME IN POLYTRAUMA - Pleva, Leopold; Sir, Milan; Mayzlik, Jaroslav (Biomedical papers, 2004)
Authors inform about the group of 8 patients with abdominal compartment syndrome (ACS) occurred as a complication in large blunt injury of abdominal cavity. To the ACS diagnose, the measurement of intracystic pressure is used routinely, whose values correlate fully with values of intraabdominal pressure (IAP). In case of increasing values of IAP over 25 mm Hg with positive clinical signs of ACS, authors indicate decompression laparotomy with temporary closing of abdominal cavity by sterile plastic foil or Ethizip. This preventive temporary laparostomy is recommended also in serious injuries of abdominal cavity in patients with fatal haemorrhage, treated by the method of staged laparotomy with tamponade of abdominal cavity and with massive blood and volume resuscitation.
Keywords: Blunt abdominal trauma/Abdominal compartment syndrome/Intraabdominal pressure/Laparostomy